ASPECTS OF THE EMERGENCE OF CHINESE DIALECTS - Anipina, А К; Saparbayeva, N B (Journal of Oriental Studies, 2016)
This article discusses the way the emergence of dialects of Chinese.Chinese dialects originated by talking with native ancient dialects and through negotiations with neighboring countries. We consider the situation of dialects in the antiquity, in the middle and in the modern period.